A Comparison of Outcomes of Proximal and Distal Anastomosis Sites of the Facial Artery in Head and Neck Reconstruction. Issue 3 (21st May 2022) - Stoehr, Jenna R.; Curran, Nicholas R.; Micallef, Christopher J.; Ellis, Marco F.
Abstract : Abstract: Recipient vessel selection in head and neck reconstruction is based on multiple factors, including defect size and location, patient history, and vessel location, diameter, and length. The authors present a comparison of proximal and distal anastomotic sites of the facial artery. A chart review of head and neck reconstructions using the facial artery as a recipient vessel over a 7-year period was conducted. The anastomosis site was identified as distal (at the inferior mandible border) or proximal (at the origin of the artery). The distal site was utilized for both defects of the midface/ scalp and of the mandible/neck, while the proximal site was exclusively used for mandible/neck defects. The following complications were included in the analysis: facial nerve injury, surgical site infection, thrombosis, flap congestion, flap loss, hardware failure, malunion/nonunion, osteomyelitis, sinus/fistula, hematoma, seroma, reoperation, and 90-day mortality. Fifty-four free tissue transfers were performed. The overall complication rate (including major and minor complications) was 53.7%. Anastomosis level did not have a significant impact on complication rate. In addition, there were no significant differences in complication rates for the distal anastomosis site when stratified by defect location. However, obese patients were more likely to have a complication than nonobese patients. This conclusion may reassure surgeons that factors related to anastomosis level, such as vessel diameter and proximity to the zone of injury, have less impact on outcomes than factors like obesity, which may inform preoperative planning, intraoperative decision-making, and postoperative monitoring.